IMPLEMENTATION OF PAI LEARNING PRACTICES IN SCHOOL DURING THE COVID-19 PANDEMIC - Rachmadilla Indah Maulidina; Udin Supriadi; Agus Fakhruddin (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
Practicum is an important part of PAI learning activities. Some research results show that PAI learning practicum is too much oriented to the cognitive aspect. This study aims to describe PAI learning at SD Negeri Cibabat Mandiri 5 by using descriptive approaches and methods. The results showed that the PAI practicum in the odd semester RPP in the even class consisted of 13 practicums covering aqidah, shari'ah and morals. Planning starts from the objectives, materials, methods, and evaluation. The facilities used are also limited. The practicum process is carried out online which includes planning, implementation, and follow-up involving teachers, students and parents. The assessment consists of practical tests, observations and assignments using several assessment tools such as the Al-Qur'an, Asmaul Husna books, PAI textbooks, prayer guide books, videos about exemplary stories of the Prophet, and Islamic cultural history books. The results of the practicum are known to all students achieving scores above the KKM.